PENGEMBANGAN POTENSI EKOWISATA BERBASIS MASYARAKAT DI HUTAN MANGROVE DESA MALIKIAN KABUPATEN MEMPAWAH - Nurhasanah, .; Erianto, .; Kartikawati, Siti Masitoh (JURNAL HUTAN LESTARI, 2018)
Malikian village is located in Mempawah Hilir District Mempawah Regency, has the potential to be developed into a community-based mangrove ecotourism area. The purpose of this study is to assess the potential of mangrove forest of Malikian village that can be developed into ecotourism area as well as to know the perception and the characteristics of the community towards the development of mangrove ecotourism. The method used to determine the potential of mangrove ecosystem is observation while the perception and characteristics of the community using survey methods with interview techniques, the respondents were determined by purposive sampling. The result of the research shows the potential of mangrove ecosystem that is there are 7 types of vegetation, as well as 11 species of animals, besides natural phenomena such as the existence of Penibung Island and Temajok Island, the sunset adds to the attraction of this region. Villagers of Malikian tend to be positive with the development plan of mangrove ecotourism potency in Malikian Village and ready to participate in ecotourism development of mangrove.Keyword : Community, Ecotourism, Malikian, Mangrove, Potential